Exchange Rate Management: The Case of Malaysia (Malaysian Management Journal, 2003)
This paper sought to examine whether Purchasing Power Parity (PPP) can become a predictor model for exchange rate. We try to determine whether at least some variant of the PPP-oriented rule may be used in Malaysia as a basis for exchange rate policy. Two methods are used to examine whether longrun PPP holds. The first method is testing whether or not the real exchange rate follows a random walk. The second is the Johansen procedure to test for a long-run relationship between real exchange rate and real economic shocks. It is found that the ringgit real exchange rate follows a random walk, which means PPP does not hold. However, supportive evidence is also seen that there is a long-run relationship between ringgit real exchange rate with current account balance and government spending. The policy implication of this important finding is that some variant of the PPP-oriented rule may be used in Malaysia as a basis for exchange rate policy. Government spending and current account balance can be used as a guide to determine the movement of real exchange rate. The error-correction model shows that real exchange rate, government spending and current account all adjusted to long-run equilibrium. It has a very important policy implication. Fiscal policy, which controls government expenditure, can be used as a tool to manage exchange rate. Measures have to be taken to increase export while at the same time import has to be reduced to maintain the current account balance to be in surplus. This will strengthen the ringgit, thus helping to stabilize the ringgit exchange rate.